Equação mestra não-linear aplicada ao estudo de bioestabilidade óptica - Yoshida, Alexandre Calzavara (Universidade Federal de São Carlos, 2004)
In this dissertation, we present a generalized master equation for a system of N two- level atoms pumped by a classical field, interacting with a reservoir. The kinds of reservoirs are assumed: (a) thermal, (b) squeezed vacuum. A master equation for the system was derived under Born and Markov approximations. The mean ¯eld approximation is done for the many-body system, so we obtain a non-linear master equation for a representative atom of the system . We discuss the optical bistable behavior of the output field, and analyze how much this phenomenon is sensitive to the number of atoms, the atom-reservoir coupling and to the parameters of de reservoir.
Keywords: Física óptica; Ótica quântica; Bioestabilidade óptica; Equação mestra; CIENCIAS EXATAS E DA TERRA::FISICA